Practica masiva contra practica distribuita: Una revision - Natalicio, Luiz F.S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A review is made of some of the many theories that have been advanced attempting to explain massed vs. distribution of practice effects. At the present time no one or group of theories has been shown adequate to explain the phenomenon. An adequate theory will have to specify the sufficient conditions which determine the facilitation that distribution of practice yields.